Розроблення режимів термічного оброблення конструкційної сталі 16х3НВФМБ-Ш для отримання низької твердості - Реброва, Олена Михайлівна; Протасенко, Тетяна Олександрівна; Шевченко, Світлана Михайлівна; Князєв, Сергій Анатолійович (Харківський національний автомобільно-дорожній університет, 2020)
У статті запропоновано технологію термічного оброблення конструкційної комплексно-легованої теплостійкої сталі 16Х3НВФМБ-Ш для отримання структури, яка забезпечує досить низьку твердість для подальшого механічного оброблення різанням.

The article proposes the technology of heat treatment of structural complex-alloy heat-resistant steel 16X3NVFMB-Sh to obtain a structure that provides a sufficiently low hardness for further machining by cutting. Problem. Due to automated production, there is a need to ensure high machinability of steel by cutting, as well as the durability of the cutting tool. To fulfill this requirement, it must be borne in mind that when annealing to a minimum strength, optimal cutting is not always achieved. Among the factor quantities that are determined by the material itself, greater importance is attached to the formation of a certain steel structure than hardness and strength. The goal of this work is to develop a heat treatment technology for structural complex of alloyed heat-resistant research steel to obtain a structure that provides a sufficiently low hardness for further machining by cutting. Methodology. To study the kinetics of changes in hardness, the experimental samples were processed according to the modes: heating at 920°C for 0.5 hours, followed by quenching in oil and tempering at temperatures of 400-750°C within 3 hours. Results. Water quenching leads to the formation of a martensite structure with a hardness of up to 45 HRC. Vacation at a temperature of 750°C for an hour forms the structure of sorbitol tempering with a hardness of 18 HRC. But such a structure does not provide high-quality machining. Originality. The results of the study made it possible to determine the heat treatment conditions of research steel, which allow it to be easily processed by cutting. Practical value. Heat treatment modes are proposed that provide a structure with a hardness of 22-26 HRC necessary for machinability.
Developing the heat treatment modes of 16H3NVFMB-Sh steel for getting low hardness
Keywords: автоматизоване виробництво; термообробка; теплостійкість; матеріалознавство; температура; heat treatment; steel structure; hardness